Endoscopic retrograde cholangiopancreatography in total situs inversus, case report with focus on endoscopic technique - Marulanda Fernandez, Hernando (2025)
This case report describes an ERCP performed on a patient with situs inversus totalis and choledocholithiasis, highlighting the technical adaptations implemented and those described in the literature to overcome anatomical challenges and achieve a successful intervention. The experience presented in this case underscores the importance of technical and the expertise of the endoscopist in managing complex procedures in patients with unusual anatomical variations.